ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN JUMLAH KEPESERTAAN BUKAN PENERIMA UPAH (BPU) PADA BPJS KETENAGAKERJAAN KANTOR CABANG JUANDA - Pradana, Dhani Rizky; Nurhadi, Nurhadi (Jurnal Bisnis Indonesia, 2024)
In Indonesia, there are still many people who do not know about social security programs for workers. Thisis because they consider contributions to be very expensive to pay and many still do not know what benefitsare provided from the BPJS Employment social security program. The Juanda Branch BPJS EmploymentOffice is quite low for registrants who work in the informal sector. Lack of information is the main cause ofdifficulties in data collection because BPU membership is very broad and the majority work in the microand small business sectors. Therefore, BPJS Employment Juanda Branch conducts socialization andeducation for the community, especially in the informal sector. The author as an intern has a goal, to helpsocialize and educate the public to know that social security for the informal sector is alsoavailable.Keywords: BPJS Employment, Marketing, Labor